Analisis Kekuatan Tarik Belah Komposit Laminat Jute sebagai Penguat Beton Kolom Silinder Berdasarkan Metode Penyerapan Energi Bahan - Lubis, Pramdya A.T.; Zulfikar, Achmad Jusuf; Iswandi, Iswandi (CV. IRA PUBLISHING, 2022)
The purpose of this study is to calculate the amount of energy that can be absorbed (toughness) of the material based on the graph of the results of the split tensile test of cylinder column concrete specimens (BKS) reinforced with laminated jute composite (KLJ) and analysis of the comparison between split tensile strength (KTB) and material toughness from the results split tensile test of BKS specimen reinforced by KLJ. The test specimens were printed based on the ASTM C496 test standard using the Vacuum Bagging method. Specimen variations consist of 1 to 4 layers of KLJ and one variation without KLJ sheath as a control specimen. The split tensile test used the UTM test tool with each variation being carried out with 3 repetitions. Calculation of Material Toughness Energy (EKB) using the Trapezoidal Numerical Integration method. The results of the study showed that giving KLJ boosters to BKS was able to increase EKB up to more than 1000% starting with 2 layers of sheathing. Thus the provision of KLJ to BKS can be recommended as a strengthening material for concrete column structures.